Threat of zoonotic malaria and strategy to overcome in Kalimantan (Indonesian Borneo) bordering Malaysian Borneo - Natalia, Diana; Handoko, Willy; Rahmayanti, Sari; Wahyudi, Tri; Abdul Rashid, Ayu Akida; Divis, Paul Cliff Simon (Universa Medicina, 2025)
Indonesia aims to eradicate malaria by 2030. Indonesia has the second highest disease burden in the WHO South-East Asia region, after India, accounting for 9% of all malaria cases in 2024. Malaria cases have dropped dramatically due to national strategic plans and programs, and the Indonesian Ministry of Health has certified several districts as malaria-free zones. Malaria cases in Kalimantan (Indonesian Borneo), have declined during the last two decades. Nearly all regencies within these provinces have been declared as having low malaria endemic status (API<1 per 1000 people), except for one regency in East Kalimantan Province, which showed a high endemicity level (API>5 per 1000 people). This reduced incidence, however, contrasts sharply with the zoonotic infection caused by the simian parasite Plasmodium knowlesi, which is prevalent in Malaysian Borneo. Only a few cases of P. knowlesi infection have been reported in South and Central Kalimantan Province since 2010. This difference between Kalimantan, Indonesia and Borneo, Malaysia appears contradictory given that both regions have a similar epidemiological risk of zoonotic malaria infection and share the same natural habitat. The references were tracked using various databases, such as Google Scholar, PubMed (MEDLINE) and other sources (Google engine and manual searching using a reference list). This review’s objective was to describe current malaria and zoonotic malaria, mosquito vector prevalence, and the available data from case reports along the Kalimantan border in Indonesia during the malaria elimination phase, compared with malaria distribution in the neighbouring country, Malaysian Borneo.